Housing satisfaction in medium- and high-cost housing: the case of Greater Kuala Lumpur, Malaysia - Tan, Teck-Hong * (Elsevier Science, 2012)
Housing policies and programs have long been implemented to ensure that all will have access to adequate housing in Malaysia. In order to achieve sustainability in the housing industry, housing providers should regulate their housing activities to suit households’ needs and wants by examining factors which account for housing satisfaction or dissatisfaction. Results showed that the degree of housing satisfaction may depend on the types of homeownership externalities that households are expected to receive, as defined by local amenities and social capital investment, and neighborhood stability of homeownership. Housing and socio-economic and demographic determinants are also found to be significant in the study. Additionally, households are generally satisfied if they are given an opportunity to purchase their homes using the Build-then-Sell 10:90 system.